SDN‐based resource allocation in MPLS networks: A hybrid approach. (9th August 2018) - Tajiki, Mohammad Mahdi; Akbari, Behzad; Mokari, Nader; Chiaraviglio, Luca
Summary: The highly dynamic nature of the current network traffics makes the network managers to exploit the flexibility of the state‐of‐the‐art paradigm called SDN. In this way, there has been an increasing interest in hybrid networks of SDN‐MPLS. In this paper, a new traffic engineering architecture for SDN‐MPLS network is proposed. To this end, OpenFlow‐enabled switches are applied over the edge of the network to improve flow‐level management flexibility while MPLS routers are considered as the core of the network to make the scheme applicable for existing MPLS networks. The proposed scheme re‐assigns flows to the Label‐Switched Paths (LSPs) to highly utilize the network resources. In the cases that the flow‐level re‐routing is insufficient, the proposed scheme re‐computes and re‐creates the undergoing LSPs. To this end, we mathematically formulate two optimization problems, ie, i) flow re‐routing and ii) LSP re‐creation, and propose a heuristic algorithm to improve the performance of the scheme. Our experimental results show the efficiency of the proposed hybrid SDN‐MPLS architecture in traffic engineering superiors traditionally deployed MPLS networks.